2017
DOI: 10.1002/mrm.26588
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time monitoring of tissue displacement and temperature changes during MR‐guided high intensity focused ultrasound

Abstract: This new fast imaging sequence provides real-time measurement of temperature distribution and displacement at the focus during HIFU ablation. Magn Reson Med 78:1911-1921, 2017. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 37 publications
2
49
0
Order By: Relevance
“…Although the majority of ARFI techniques have been demonstrated in phantoms and ex vivo tissues, in vivo studies recently have been published as well. Depending on the application, MR‐ARFI scan time has been reduced using keyhole or parallel imaging techniques when multiple MR radiofrequency (RF) coils are available .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of ARFI techniques have been demonstrated in phantoms and ex vivo tissues, in vivo studies recently have been published as well. Depending on the application, MR‐ARFI scan time has been reduced using keyhole or parallel imaging techniques when multiple MR radiofrequency (RF) coils are available .…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between changes in tissue mechanical properties and thermal dose has been investigated using both ultrasound (US) and MR imaging . For MRI assessment of tissue mechanical properties, this typically has been accomplished using a standalone MR‐ARFI sequence, but methods for acquiring simultaneous MR‐ARFI and PRF thermometry have been proposed .…”
Section: Introductionmentioning
confidence: 99%
“…36,38,[41][42][43][44][45] Methods to simultaneously measure tissue displacement with MR-ARFI and tissue temperature change using the PRFS method have further been described. 34,36,46,47 Although MR-ARFI has been used previously to interrogate changes in tissue stiffness, these measurements have only been performed for 1 small focal region. To use tissue stiffness changes to determine the treatment endpoint, it will likely be necessary to interrogate a larger volume of tissue, which will be far too time-consuming to perform with existing MR-ARFI techniques.…”
Section: Magnetic Resonance In Medicinementioning
confidence: 99%
“…The decrease in displacement of approximately 22% after ablation agrees well with what has been reported previously in ex vivo muscle. 47 For in vivo experiments, it has been found that rat brain became softer and rat leg muscle became stiffer with high thermal dose, indicating that different tissues may respond differently with thermal treatment. 66,67 Although this agreement with the literature regarding ex vivo studies is encouraging, more ex vivo and especially in vivo experiments are needed to draw any real conclusions about how the tissue mechanical properties change with clinically relevant ablations.…”
Section: Magnetic Resonance In Medicinementioning
confidence: 99%
See 1 more Smart Citation